Diagnostic Role of Contrast Enhanced Computed Tomography (CECT) of Abdomen and Pelvis in Evaluation of Colon Pathologies (Nepalese Journal of Radiology, 2025)
Introduction: Contrast-enhanced computed tomography (CECT) plays an important role in distinguishing benign and malignant colon lesions through cross-sectional evaluation of pericolonic abnormality and features such as wall thickening, post-contrast enhancement, lymphadenopathies, and other associated findings. This can help in the early diagnosis and treatment of colon lesions. Though colonoscopy is the gold standard, it has various limitations and is an invasive procedure.Methods: A retrospective study was carried out in patients with large bowel symptoms who had undergone CECT from October 2020 to January 2025 at Patan Hospital, Lalitpur, Nepal. Ethical approval was obtained from the institutional review committee of Patan Academy of Health Sciences. CECT diagnosis based on bowel wall thickening and associated features was compared with histopathology diagnosis, and the sensitivity, specificity were calculated.Results: Among 356 patients, 260 had benign and 96 had malignant lesions. The sensitivity and specificity of CECT in diagnosing malignant colon lesions were 78.1% and 83.1% respectively. Ascending colon (35.41%) and recto sigmoid region (36.4%) were the most common sites for malignancy, while cecum (45.38%) was the common site for benign lesions. CECT features of colon malignancy were asymmetrical wall thickening, focal involvement, heterogeneous enhancement, lymphadenopathy, exophytic component, and intestinal obstruction.Conclusions: CECT helps in non-invasive evaluation of colon lesions with early detection of malignancy, disease staging and treatment through lesion morphology and pericolonic extent. While colonoscopy and histopathology remain the gold standard for diagnosis.